Association between rational and irrational beliefs and life satisfaction: a systematic review with meta-analysis - Oscar Gómez-González; Nancy Pamela Castro Zazueta; Felipe Santoyo-Telles; Fabiola González Betanzos (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2023)
Rational Emotive Behavioral Therapy (REBT) is a psychotherapy whose aim is to improve well-being by decreasing irrational beliefs (IBs) and increasing rational beliefs (RBs). The REBT is implemented internationally, but few studies validate its theoreti-cal assumptions, particularly on positive psycholo-gical variables, such as life satisfaction (LS). The aim was to analyze if the evidence corroborates the theoretical assumptions of the REBT, where the SV should be negatively associated with the IBs, and positively with the RBs. A systematic review with meta-analysis based on the PRISMA statement was performed. Studies from any date that statistically estimated the association between RBs and IBs with LS, in any population, were included. 11 stu-dies met the inclusion criteria. The results show contradictions to the assumptions of the REBT. Some RBs and IBs were not significantly associa-ted with LS, and even some IBs positively predic-ted SV. In conclusion, future studies could corrobo-rate these results and suggest relevant updates to the REBT assumptions.